The Investigation of Physical Properties of Composite Fertilizer Including Boron Micro Element - Havva Mumcu Şimşek; Rövşen Guliyev (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Fertilization is one of the most common applications in agricultural fields for achieving high yield. Fertilizer is the important input of agriculture. Raw material costs are nearly 80% of the production costs in chemical fertilizers. Because of high prices, fertilizer usage has started to decrease. The utilization of industrial wastes in the production reduces the costs. Not only is fertilizer expenditure significant, but also the physical properties should be considered. In this study, the physical characteristics of composited fertilizer containing boron which was obtained from the reaction between the diammonium phosphate and borogysum industrial waste were examined. Under laboratory conditions, diammonium phosphate was composited with borogysum at the mole ratio of 1:1 and during this process, the solid/liquid (S/L) ratio, temperature, time, pH of the pulp and speed were 1/3, 40°C, 90 min, 5.5 and 500 rpm respectively. The moisture content, grain (granule) size, tight and loose volume weights, granular fracture resistance and the agglomeration angle of the new product including boron were evaluated. As a consequence, the grain size was in range of 3 and 4 mm, loose volume weight was 1363.32 kg/m3, the granular fracture resistance was 2.92 kg/granule, agglomeration angle was 89.9 kg/granule and Granulometric Spread Index (GSI) and Uniformity Index (UI) were recorded as 16 and 76.9. These findings were compatible with National and International Standards.